Dual Transcriptional Profiling of Carrot and ‘Candidatus Liberibacter solanacearum’ at Different Stages of Infection Suggests Complex Host-Pathogen Interaction - Jinhui Wang; Minna Haapalainen; Anne I. Nissinen; Minna Pirhonen (Molecular Plant-Microbe Interactions, 2021)
The interactions between the phloem-limited pathogen ‘Candidatus Liberibacter solanacearum’ haplotype C and carrot (Daucus carota subsp. sativus) were studied at 4, 5, and 9 weeks postinoculation (wpi), by combining dual RNA-Seq results with data on bacterial colonization and observations of the plant phenotype. In the infected plants, genes involved in jasmonate biosynthesis, salicylate signaling, pathogen-associated molecular pattern- and effector-triggered immunity, and production of pathogenesis-related proteins were up-regulated. At 4 wpi, terpenoid synthesis-related genes were up-regulated, presumably as a response to the psyllid feeding, whereas at 5 and 9 wpi, genes involved in both the terpenoid and flavonoid production were down-regulated and phenylpropanoid genes were up-regulated. Chloroplast-related gene expression was down-regulated, in concordance with the observed yellowing of the infected plant leaves. Both the RNA-Seq data and electron microscopy suggested callose accumulation in the infected phloem vessels, likely to impair the transport of photosynthates, while phloem regeneration was suggested by the formation of new sieve cells and the upregulation of cell wall–related gene expression. The ‘Ca. L. solanacearum’ genes involved in replication, transcription, and translation were expressed at high levels at 4 and 5 wpi, whereas, at 9 wpi, the Flp pilus genes were highly expressed, suggesting adherence and reduced mobility of the bacteria. The ‘Ca. L. solanacearum’ genes encoding ATP and C4-dicarboxylate uptake were differentially expressed between the early and late infection stages, suggesting a change in the dependence on different host-derived energy sources. HPE1 effector and salicylate hydroxylase were expressed, presumably to suppress host cell death and salicylic acid-dependent defenses during the infection.[Graphic: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.